(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article presents metaphorical memory models as the most productive in the Ukrainian diary discourse. Ukrainian diary discourse definitely topographs the general map of the memory of the world in which the diarist lived. Through the prism of his own consciousness he marks the present and denotes himself in it. Separate segments – diarrheal, autobiographical, written, generational, as if puzzles are a common memory card, each of which films a single fragment through the prism of the diary writer vision. Defined metaphors of memory are outlined by special markers, which not only visualize the diary text fabric, but also form its skeleton. The expressive verbalizers in the metaphorical memory model are the following frames: «душа пам’ятає», «мати перед очима»; «стояти перед очима», «вертатися думками», «постати перед нею», «спливати в пам’яті», «змигнути в пам’яті», «не виходити з пам’яті», «політати думками понад бідною Україною», «озватися звідти, з дитинства, юності», «не запектися в душі», «міцно врізатися в пам’ять», «увібрати в душу, запам’ятати, зберегти в пам’яті», «пропливати перед очима», «зринати з глибин пам’яті», «зостатися в душі» etc. The following metaphorical images-comparisons have been singled out: «пам’ять – свічка», «пам’ять – рослина»; they constitute the opposition abstract – concrete. Significant and adverbial metaphorical models indicating memory processes have been identified. Complex metaphorical constructions, such as «той сором живе в мені» are used as the means of expressivity contributing much to the emotional and figurative conveying of the diary writer’s thoughts. Metaphorical potential of the phrase «думки звертаються до тих, кого давно нема» not only causes emotions associated with past events in the life of a diary writer. These emotions are alive and they simulate his linguistic space, contribute to the creation of a certain picture of the world with the corresponding reactions to them, provide the reliability of the reproduced information. Memory is not just a resource (archival repository) of everything experienced by a diarist, not just information, emotions, skills and abilities, words, categories, but also the contradictory process of Ego’s communication with himself, with his constantly distancing past. It is proved that memory is the sum of all knowledge of the diarist about the world and about himself. The metaphorical model of memory in a diary discourse should be formed with the consideration of such mental concepts as thought, suggestion, consciousness, desire, and doubt.